Myopia the global progressive healthproblem: Are wereadingtoomuch? (Bangladesh Journal of Medical Science, 2017)
Myopia is becoming a global public health problem in our society. The global progression of myopia might develop due to near work activities (reading, writing, homework, computer) and less outdoor activities. Recent studies show that beside genetic component, geography and ethnicitiy do have also an impact in the development and progression of myopia.Bangladesh Journal of Medical Science Vol.16(3) 2017 p.337-338